Large area perovskite solar cell module. (January 2017) - Cai, Longhua; Liang, Lusheng; Wu, Jifeng; Ding, Bin; Gao, Lili; Fan, Bin
Abstract: The recent dramatic rise in power conversion efficiencies (PCE) of perovskite solar cells has triggered intense research worldwide. However, their practical development is hampered by poor stability and low PCE values with large areas devices. Here, we developed a gas-pumping method to avoid pinholes and eliminate local structural defects over large areas of perovskite film, even for 5 × 5 cm 2 modules, the PCE reached 10.6% and no significant degradation was found after 140 days of outdoor testing. Our approach enables the realization of high performance large-area PSCs for practical application.